A Spin-controlled Microcavity Laser - Hsu, Feng-Kuo; Xie, Wei; Lee, Yi-Shan; Lin, Sheng-Di; Lai, Chih-Wei (My University, 2015)
We demonstrate highly circularly polarized lasing under non-resonant elliptically polarized optical pumping in a semiconductor microcavity at room temperature. (C) 2014 Optical Society of America